2021
DOI: 10.1016/j.renene.2021.04.112
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation on the volute cutwater for pumps running in turbine mode

Abstract: The hydropower sector has recently raised the interest in pump as turbine (PaT) that can be a valid tradeoff between capital cost and performance in micro-scale installations. Nevertheless, the modest efficiency of PaTs often restricts their exploitation. In this paper, available experimental data are used to tune a numerical model which aims to investigate the effect of the pump cutwater design on the PaT performance to improve the hydraulic efficiency. Because of its finite thickness, the cutwater interferes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…Nevertheless, CFD data are showing discrepancies compared to experimental data. CFD versus experimental data discrepancies may come from geometry simplification performed in CFD studies [38] . In addition to the above, accuracy of CFD methods depends on parameters such as mesh quality, turbulence model and boundary conditions [39] , [40] , [41] .…”
Section: Short Overview Of Pat Performances Prediction Methodsmentioning
confidence: 99%
“…Nevertheless, CFD data are showing discrepancies compared to experimental data. CFD versus experimental data discrepancies may come from geometry simplification performed in CFD studies [38] . In addition to the above, accuracy of CFD methods depends on parameters such as mesh quality, turbulence model and boundary conditions [39] , [40] , [41] .…”
Section: Short Overview Of Pat Performances Prediction Methodsmentioning
confidence: 99%
“…The throat area and shape of volute cutwater (or so called volute tongue) are of great importance for PaT operation since the flow angle given by the volute must be processed at the impeller inlet [11]. For the pump investigated in this study the flow angle given by the volute throat area is estimated to be α 3 = 16°, which is the average value between upper wall angle (23°) and lower wall angle (9°) of throat area, see figure 3.…”
Section: Pump Parametersmentioning
confidence: 99%
“…As expected, unsteady flow phenomena such as the backflows, shock flows, and vortical flows, have inflicted higher entropy and energy dissipation, where flow zones with the highest energy losses have been pointed out as the vicinities of the blade leading edge, the cavity zone (impeller's back and front chambers), and volute throat. In the same respect, Guan et al [31] and Morabito et al [32] found that the position and geometry of the volute throat may influence the machine energy loss characteristics and its efficiency.…”
Section: Introductionmentioning
confidence: 96%